A UNICEF's Protective Role for Child Victims of War in Ukraine - Arhevan, Arlief; Tunggal, Aprilia Restuning (UNIDA GONTOR, 2023)
The conflict that erupted in Ukraine on February 24, 2022, had a devastating impact on the people caught in the middle of the fighting, especially children. The conflict forced many of them to flee their homes, resulting in a population decline, and exposing them to a range of threats from surrounding countries, including human trafficking, slavery, organ sales, and other forms of exploitation. The primary objective of this research is to examine the role of UNICEF in protecting child victims of war in Ukraine due to the Russian-Ukrainian conflict. To achieve this, the study uses a descriptive qualitative method, including data collection through literature reviews, including journals, books, and other related literature. It also applies the concepts of transnational crime and child protection as regional security analysis tools. The study's results reveal that child protection is essential to ensure children's rights are safeguarded, and they can live in a safe and stable environment, free from the dangers of war. To this end, UNICEF has been working closely with other international organizations, such as UNHCR, to provide support to refugee children through the Blue dots program. UNICEF has taken significant steps to mitigate the impact of the conflict on children, including providing emergency assistance, establishing temporary learning centers, and offering psychosocial support.